ANALISA DAYA MOTOR INDUKSI 3 FASA SEBAGAI PENGGERAK CONVEYOR DI PT. PESONA KHATULISTIWA NUSANTARA - Rizky Ramadhan; Linda Sartika (Elektrika Borneo, 2023)
Induction motor has become one of the tools that are needed for companies especially in the industrial world, which has used as a driving tool to deliver finished raw materials or raw materials such as coal. In PT. Pesona Khatulistiwa Nusantara, the use of an induction motor was applied to the conveyor of BC-01 and BC-03 conditions where the coal mine was operating. The motor continues to move the conveyor in order to move the coal to the place that had been provided for up to 24 full hours. Thus, it was necessary to analyse the power of consumption and the level of efficiency of the motor on the conveyor of BC-01 and BC-03, because if there was damage, the production process would be hampered. Motor efficiency was obtained by calculating in advance the value of input power and output power. The primary data was obtained by direct measurements to the field directed by the company’s electrical employees by varying the condition of the coal load on the conveyor of 0%, 50% and 100% and the results of the calculation from the input power and the output power of BC-01 and BC-03 motors whose values were not much different, thus the efficiency of BC-01 and BC-03 conveyor motors ranges from 99% to 100%. Therefore, the use of an induction motor as a conveyor BC-01 and BC-03 in PT. Pesona Khatulistiwa Nusantara was very good. The efficiency of an induction motor was obtained from the value of the input power and output power, so the condition where the efficiency was declared good if the input power value was close to the value of output power.